Advancing knowledge on the paleoproductivity and climate in the Guaymas Basin, Gulf of California, over the past 31,200 years: geochemical proxies in IODP expedition 385 sediments - Aldama-Cervantes, Alejandro; Pérez-Cruz, Ligia; Urrutia-Fucugauchi, Jaime; Monreal-Gómez, María Adela; Merino-Ibarra, Martín; Velázquez-Aguilar, Mauricio; Venegas-Ferrer, Rafael; Sanchez-Cabeza, Joan Albert; Sifeddine, Abdelfettah; Höfig, Tobias W. (Frontiers in Earth Science, 2025)
The Guaymas Basin (GB) is a highly productive region in the Gulf of California. Subseafloor sedimentary amorphous bio-opal and Ba/Ti records obtained from its northwestern and central areas reveal significant changes in exported productivity over the past 31,200 years. Millennial-scale variability reflects the influence of wind-driven upwelling, mesoscale eddies, and shifts in climate variability operating at orbital, millennial, and centennial timescales. Spatial heterogeneity in productivity recorded in International Ocean Discovery Program boreholes highlights regional differences in process dominance. We identify seven distinct productivity phases: From ∼31,200 to ∼26,500 cal yr BP, laminated sediments indicate strong seasonal variability and high productivity due to intense upwelling activity caused by northwesterly winds linked to a southward-shifted Intertropical Convergence Zone. The Last Glacial Maximum, from ∼26,500 to ∼19,000 cal yr BP., displayed pronounced fluctuations and a slight decline in productivity compared to the previous interval, owing to the reduced influence of the North Pacific High on the GB during this period. From ∼19,000 to ∼11,700 cal yr BP, there were shifts of high and low productivity, with opal minima coinciding with Heinrich events 2 and 1, as well as the Younger Dryas. Productivity declined slightly between ∼11,700 and ∼7,000 cal yr BP, featuring a short high-productivity period within that timespan (∼10,500 to ∼10,300 cal yr BP). From ∼7,000 to ∼4,200 cal yr BP, productivity decreased in the NW and increased in the central basin. This contrast reflects enhanced winter-spring coastal wind-driven upwellings and reduced eddy activity in the west. From ∼4,200 to ∼130 cal yr BP, productivity increased in both studied areas. The sedimentary Ba/Ti values in both holes generally indicate lower levels during the cold glacial period and higher levels during the warm interglacial period, suggesting reduced biological barite accumulation and less organic matter export from the surface under cold climate conditions. These changes correspond to documented climate transitions, highlighting GB’s sensitivity to global forcings (e.g., ice sheet retreat) and regional ocean-atmosphere interactions. Our findings underscore the key role of dynamic physical processes in shaping long-term productivity patterns in marginal seas at high resolution.